1975
DOI: 10.1161/01.cir.52.2.245
|View full text |Cite
|
Sign up to set email alerts
|

Mitral valve prolapse and coronary artery disease. Clinical, hemodynamic, and angiographic correlations.

Abstract: SUMMARYAmong 95 patients with angina pectoris and angiographically documented coronary artery disease (CAD), prolapse of the scallops of the posterior leaflet of the mitral valve (PLMV)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1977
1977
1996
1996

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Verani et al [34] and Raizada et al [29] have also reported a high incidence of prolapse of the mitral valve among patients with coronary artery disease. Papillary muscle dys function, secondary to coronary artery disease, has been reported to pro duce prolapse of the mitral valve [2,6,17,33]. In the series of Verani et al [34], as in ours, some patients were not suspected of having pro lapse of the mitral valve prior to cardiac catheterization.…”
Section: Association Of Coronary Artery Disease and Mitral Valve Prolsupporting
confidence: 47%
See 2 more Smart Citations
“…Verani et al [34] and Raizada et al [29] have also reported a high incidence of prolapse of the mitral valve among patients with coronary artery disease. Papillary muscle dys function, secondary to coronary artery disease, has been reported to pro duce prolapse of the mitral valve [2,6,17,33]. In the series of Verani et al [34], as in ours, some patients were not suspected of having pro lapse of the mitral valve prior to cardiac catheterization.…”
Section: Association Of Coronary Artery Disease and Mitral Valve Prolsupporting
confidence: 47%
“…Significant coronary artery disease was considered to be present when one or more of the major coronary arteries had 70% or more narrowing of the diameter of the vessel in one dimension. Viewed from different projections prolapse of the mitral valve was judged to be present when there was definite abnormal systolic bulge of one or both leaflets into the left atrium [2,[29][30][31], Posterior mitral valve leaflet prolapse produced most commonly three well-defined scallops [15,22,29,30], Oc casionally, only one or two scallops were seen in the RAO projection [29, 30J. Anterior mitral valve leaflet prolapse was seen as a hump on the anterior surface of the ventricle just beneath the aortic root [15], or as a double density overlapping one or more of the scallops of the posterior leaflet [30], In the LAO projection, the prolapse of the anterior leaflet produced abnormal bulge with its fullicrum attached to the aortic root. Arbitrarily, the degree of mitral valve prolapse was classified into three grades of severity: mild, moderate and severe ( fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 ' M Systemic hemodynamic findings in patients with mitral valve prolapse have been reported to be normal unless a significant degree of mitral regurgitation is present. 12 …”
mentioning
confidence: 99%
“…The association of mitral valve prolapse with obstructive coronary disease is recognised yet controversial (Davis et al, 1971;Steelman et al, 1971;Cheng, 1972;Gooch et al, 1972;Liedtke et al, 1973;Scampardonis et al, 1973;Jeresaty, 1973Jeresaty, , 1975Aranda et al, 1975;Gentzler et al, 1975). Some investigators (Cheng, 1972) maintain that coronary artery disease can produce mitral ballooning by virtue of papillary muscle ischaemia or fibrosis.…”
mentioning
confidence: 99%